Price Discovery in Floor and Screen Trading Systems - Erik Theissen (University of Bonn, Bonn Graduate School of Economics (BGSE), 2001)
We analyze price discovery in floor-based and electronic exchanges using data from the German stock market. We find that both markets contribute to price discovery. There is bidirectional Granger causality, and prices from both markets adjust to deviations from the long-run equilibrium. We use two different measures of the contributions to price discovery, the information share (Hasbrouck 1995) and the weights with which the series enter the common long memory component as defined by Gonzalo / Granger (1995). The contributions of the two trading systems to the process of price discovery are almost equal when transaction prices are used for the estimation. Models based on quote midpoints indicate that the electronic trading system has a larger share in the price discovery process. A cross-sectional analysis reveals that the contributions to price discovery are positively related to the market shares of the trading systems.
Keywords: G10; 330; Floor versus screen trading; Error correction; Information shares; Common long memory components